Corporate Acquisitions and Firm-Level Uncertainty: Domestic Versus Cross-Border Deals - Ye Bai; Sourafel Girma; Alejandro Ria\~no (Center for Economic Studies and ifo Institute (CESifo), 2020)
This paper studies the impact of corporate acquisitions - both domestic and cross-border - on the uncertainty faced by acquiring firms. We use data for UK publicly-listed firms from 2004 to 2017 and employ a matching estimator combined with difference-in-differences to control for the endogenous selection of firms into buying other companies. We find that acquisitions exert a large and persistent effect on the volatility of stock returns of acquirers and that this response is crucially determined by the geographic scope of the acquisitions firms undertake. We find that the impact of acquisitions on firm-level uncertainty is characterized by a pecking order: the announcement of a domestic takeover leads to a reduction in the uncertainty faced by the acquirer, while cross-border acquisitions - particularly those involving target firms in emerging markets - engender a positive response in acquirers' volatility. Our results suggest that acquisitions affect uncertainty because they change firms' exposure to shocks - as they expand their operation in new markets - and also because they are large and risky investments whose returns take time to materialize.
Keywords: G32; G34; F23; F36; 330; mergers and acquisitions; uncertainty; volatility; globalization; stock returns; UK